The essence of a systematic approach in designing independent work of students as an intellectual factor of learning (Pedagogy of Higher and Secondary Education, 2021)
The essence of a system approach at designing of independent work of students as intellectual factor of training is opened in this article.
Keywords: a system approach; independent work; designing of independent work; the intellectual factor